The Roles of Mast Cells in Parasitic Protozoan Infections - Lu, Fangli; Huang, Shiguang (Frontiers in Immunology, 2017)
Protozoan parasites, such as Plasmodium spp., Leishmania spp., Trypanosome spp., and Toxoplasma gondii, are major causes of parasitic diseases in both humans and animals. The immune system plays a critical role against protozoa, but their immune mechanism remains poorly understood. This highlights the need to investigate the function of immune cells involved in the process of parasite infections, and the responses of host immune system to parasite infections. Mast cells (MCs) are known to be central players in allergy and anaphylaxis, and it has been demonstrated that MCs have crucial roles in host defense against a number of different pathogens, including parasites. To date, there are many studies that have examined the interaction of helminth-derived antigens and MCs. As one of the major effector cells, MCs also play an important role in the immune response against some parasitic protozoa, but their role in protozoan infections is, however, less well characterized. Herein, we review the current knowledge about the roles of MCs, and their mediators, during infections involving highly pathogenic protozoa including Plasmodium spp., Leishmania spp., Trypanosoma spp., and T. gondii. We offer a general review of the data from patients and experimental animal models infected with the above mentioned protozoa, which correlate MCs and MC-derived mediators with exacerbated inflammation and disease progression as well as protection against the parasite infections under some conditions. This review updates our current understanding of the roles of MCs during parasitic protozoan infections, and the participation of MCs in parasitic protozoan infections could be of a potential therapeutic target.